Lived space and the landscape of emotions in Vincent Van Gogh's “L’Arlésienne” (PerCursos, 2021)
This article presents the results of a study on life experiences and landscapes in Vincent van Gogh's “L’Arlésienne”. The study addresses said painting as a landscape of emotions, shaping Vincent van Gogh's existence and providing sense and meaning based on his experiences in his living space. In this sense, we consider that the space portrayed in Vincent van Gogh’s paintings is constituted as landscapes that, as symbolic forms, shape the artist’s life. Thus, we consider that the symbolic space attributes sense and meaning to the way space is experienced and represented by subjects.
Keywords: symbolic forms; lived space; landscape; Vincent Van Gogh